Accumulation of phenanthrene and its metabolites in lettuce (Lactuca sativa L.) as affected by magnetic carbon nanotubes and dissolved humic acids. Issue 12 (3rd November 2020) - Jia, Weili; Ma, Chuanxin; Yin, Mengfei; Sun, Hongwen; Zhao, Qing; White, Jason C.; Wang, Cuiping; Xing, Baoshan
Abstract : Accumulation and metabolites of phenanthrene in lettuce as affected by magnetic carbon nanotubes and dissolved humic acids were investigated under hydroponic conditions. Abstract : This study investigated the behavior of phenanthrene (Phe) in lettuce ( Lactuca sativa L.) as affected by carbon nanotubes (CNTs)/magnetic carbon nanotubes (MCNTs) and dissolved humic acids (DHAs) under hydroponic conditions for 10 days. MCNTs alone or combined with DHAs reduced Phe accumulation in roots by more than 50%; in shoots, CNTs increased the Phe accumulation from 72.1 to 114.8%, regardless of the presence of DHAs. DHAs decreased the total Phe metabolites content in lettuce by 21.7–98.9%. Nine Phe-related metabolites were identified and a possible Phe metabolism pathway in lettuce was proposed. A positive correlation was found between Fe and Phe content in lettuce under treatments of MCNTs/CNTs combined with DHA1, indicating exogenous Fe in conjunction with DHA1 affected Phe accumulation in lettuce. Additionally, MCNTs/CNTs and DHAs reduced Phe-induced toxicity to lettuce by elevating the activity of shoot glutathione S -transferase (GST). The addition of MCNTs/CNTs alone and combination with DHAs enhanced photosynthesis. The upregulation of genes related to photosynthesis and carotenoid biosynthesis in the treatments with DHAs or the combinations of CNT/MCNTs and DHAs alleviated Phe-induced phytotoxicity and negative impacts on photosynthesis. Our findings provide important information on Phe accumulation and its metabolism in plant–soil systems and on the roles of DHAs and MCNTs in alleviating the contaminant-induced phytotoxicity.